Ovarian Follicular Development Study in Jersey Crossbred Cows Reared in India - Lakshmikantan, Uthandaraman; Selvaraju, Mani; Mathivanan, Rangasamy; Geetha, Thangavel; Periyannan, Mani; Ruthrakumar, Ravichandran (The Indian Journal of Animal Reproduction, 2023)
Ovarian follicular wave pattern studies provide the basis for applying reproductive intervention for improving fertility  and improving the success of embryo transfer programmes in cattle. Four apparently healthy non-pregnant, pluriparous  crossbred Jersey cows reared in a local farm located at Tirupur were utilized for this study. The evaluation was performed  more than one plane, and all the measurable follicles (>3mm) were counted and recorded every other day. Various  follicular dynamics related parameters were studied such as day of wave emergence, dominant follicle, static phase of  dominant follicle, regressing phase of dominant follicle, day of maximum diameter, maximum size, duration of growth,  growth rate, duration of atresia, rate of atresia and duration of detection. The Ultrasonographic evaluation was performed  every other day throughout an estrous cycle starting from observed estrus (Day 0) to the subsequent standing estrus.  A total of 10 normal estrous cycles were monitored for follicular wave pattern, in which 8 out of 10 (80 per cent) were  two wave and 2 out of 10 (20 per cent) were three wave estrous cycles. The mean length of 2-wave estrous cycle was  19.25±0.41 days and 3-wave estrous cycle was 21.50±0.50 days. It was concluded that Jersey crossbred cows frequently  had 2 wave estrous cycle with pre-ovulatory follicle size 12.62±0.94mm with the growth rate of 1.13±0.12mm/day and  the size of pre-ovulatory follicle in 3-wave estrous cycle was lower (10.75±1.25mm) than 2-wave estrous cycle.
Keywords: Follicular dynamics; Follicular waves; Jersey crossbred cows